The strain-7 study: multimodal, multivendor, multifield strength, scan:rescan comparison of global longitudinal and circumferential strain in healthy volunteers. (8th February 2021) - Nazir, MS; Yazdani, M; Draper, JANE; Franks, R; Lam, S; Plein, S; Kapetanakis, S; Young, A; Chiribiri, A
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): National Insitute for Health Research Background There is clinical and prognostic evidence for global longitudinal strain (GLS) and circumferential strain (GCS). A range of techniques exist: 2-dimensional echocardiography (2Decho), 3-dimensional echocardiography (3Decho) and Cardiovascular Magnetic Resonance (CMR). Purpose To investigate inter-study repeatability and inter-method comparison of GLS and GCS techniques. Methods Volunteers underwent same day scan: rescan 2Decho, 3Decho, 1.5T Siemens CMR (Cine imaging and Displacement encoding with stimulated echoes [DENSE]), 3T Siemens CMR (Cine Imaging and DENSE) and 3T Philips CMR (Tagging and Fast strain-encoding [fSENC]) imaging. Strain was quantified for 2Decho (EchoPAC), 3Decho (TomTec), Feature tracking (FT) for cine imaging (CircleCVI), CIM (University of Auckland) for DENSE and Tag, and Myostrain (Myocardial solutions) for fSENC. Results 20(6F) volunteers, mean age 33 ± 7 years, mean LVEF 62 ± 4%. All GLS and GCS methods had excellent inter-study agreement (ICC > 0.75) with coefficient of variation (CoV) between 4-8% (Table 1). Median and IQR are presented in Figure 1. Friedman's test revealed statistically significant inter-method differences for GLS (χ2 = 66.4, p < 0.0001) and GCS (χ2 = 50.9, p < 0.0001). Post hoc analysis using Dunn's test with Bonferroni correction demonstrated significant differences: -GLS: 2Decho vs DENSE 1.5T (p = 0.001) and Myostrain 3T (p = 0.0116); 3Decho vs FT 3T (p = 0.049) and DENSE 1.5T (p < 0.0001); FT 1.5T vs DENSE 1.5T (p = 0.001) and Myostrain 3T (p = 0.01); FT 3T vs Myostrain 3T (p < 0.0001); DENSE 1.5T vs Tag 3T (p = 0.0008) and Myostrain 3T (p < 0.0001); Tag 3T vs Myostrain (p = 0.02). -GCS: 3Decho vs DENSE 1.5T (P = 0.0005), FT 1.5T (p < 0.001), FT 3T (P < 0.001) and Myostrain (p = 0.003); FT 1.5T vs Tag 3T (p = 0.001), FT 3T vs Myostrain 3T (p = 0.04). Conclusion: There is excellent interstudy agreement for GLS and GCS methods. However, there are important inter-method differences in absolute values, that need to be considered for clinical application as a surveillance method and longitudinal studies.